ANALISIS SISTEM PELAPORAN PADA KOPERASI KARYAWAN SEJAHTERA PDAM TIRTA JATI DI SUMBER KABUPATEN CIREBON - mustakim mustakim; Siska mariawati; Wiwin kurnia; Lukman nul hakim; Siti Nila Rokhmana (IAIC (Institut Agama Islam Cirebon), 2020)
Coorperative as a form bussines entity are inportand in easing economic growth,because currently coorporatives are an alternative for the community to obtain fund in an effort to improve living standards,fulfill daily need and develope businesses. The savings and loan system at the Tirta Jati prosperous employee coorporative PDAM still uses manuals so it requires a system that supports and provides more satisflying services for coorporative members such as applications web so as to produce a data management system in an easier way,effective,and efficient starting from the existence of master data transaction data to the formation of reports. With this system,data security is safer because login validation is made in terms of data storage it is more secure and neat,in finding data easier,and in presenting the required data more quickly and accurately.